INTERNATIONAL HUMAN RIGHTS STANDARDS AND THE RIGHT TO PRIVACY IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2019)
The author of than article gives analyze of important international standards in sphere of secure human rights in RK. More than,the author says about the main international norms of secure inviolability of private life.